THE ROLE OF MULTIMEDIA IN ISLAMIC TEACHING PROPAGATION (DA’WAH): An Indonesian Experience - Gunawan Adnan (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2019)
This study is aimed at elaborating the role of multimedia in spreading out Islamic teaching among Muslim society, particularly as it is practiced and experienced in Indonesia. It is found that high technology, particularly information technology extraordinarily influence almost all aspects of human life. The development of technology has indeed contributed to the emergence of various inventions and simplified human daily lives, including the methods of preaching Islamic teaching to the Moslems. This research finds out that there are many programs and strategies of doing da’wah (Islamic teaching propagation) and developing its methods, among others, by utilizing multimedia both electronic and printed, both digital and non-digital ones. This sort of program integrates different kinds of media, such as, radio, television, text, internet, picture, MP3, animation, narration, video, and music and others. Another important role of this multimedia is to strengthen interactive and communicative ability and attitude between the da’i (propagator/communicator) and his/her mad’u (communicant/audience). By utilizing multimedia the so-called ummah (moslem society) would not only get information passively but also could select information they need and like based on sort of media they like. In other word, this program generates the intense relationship between the da’i (the da’wah doer/preacher) and the media. This program is very important to develop the strategies of spreading Islamic teaching among Muslim society in order to cope with the impact of high technology.Keywords : Multimedia and Islamic Teaching Propagation